PROTOCOL: Criminal justice interventions for preventing terrorism and radicalisation: An evidence and gap map. Issue 3 (1st September 2022) - Sydes, Michelle; Hine, Lorelei; Higginson, Angela; Dugan, Laura; Mazerolle, Lorraine
Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows: to identify the existing evidence that considers the effectiveness of criminal justice interventions in preventing terrorism and radicalisation and to identify existing gaps in the evidence where new primary research could be undertaken and where future synthesis could be conducted.